Responsibility of/in digital transformation - Zimmer Markus P.; Järveläinen Jonna; Stahl Bernd C.; Mueller Benjamin (Elsevier, 2025)
In this editorial, we chart a path for research on responsible digital transformation (DT). We draw on responsible innovation to provide a framework that can inform the research agenda of the emerging literature of responsible DT. First, we outline what we refer to as DT and how the existing debate overlooks key issues for making DT responsible. Second, we draw on the concept of responsible innovation to examine the meaning of responsibility in the context of innovation and translate it to DT. This leads us to understand responsible DT as two-dimensional including a process and an outcome dimension. Accordingly, we pose two questions: (1) when we can consider a DT process responsible (i.e., responsibility in DT), and (2) when we can consider DT outcomes responsible (i.e., the responsibility of DT). Offering suggestions on how we can approach studying these questions, we chart a path for responsible DT research. This path presents a new frontier within the DT discourse calling to our attention how DT—if we make responsibility of/in DT explicit—can be the solution rather than the problem.